Sport and Social Development: Evaluating a Professional Sport League’s Domestic Violence and Sexual Abuse Camp - Stephen Hills; Matthew Walker (Journal of Applied Sports Management, 2017)
We explore the use of sport to address the sensitive issue of domestic violence and sexual abuse (DVSA) by evaluating a professional sport league’s pilot DVSA Camp in the United Kingdom. The league served as a hook to engage target groups before using the sport as an analogy to educate on DVSA. We found the DVSA camp had a limited effect on participants’ knowledge about and beliefs toward DVSA, but was able to engage an at risk target group and increase awareness of DVSA. Certainly, greater engagement is required to address serious social issues if behavioral change is the goal. We feel the program was well intended and served as a strategic positioning mechanism for the professional sport league. However, a broader and more long-term focus on developmental outcomes should be sought. Subscribe to JASM
Keywords: Sport-for-development; domestic violence; sexual abuse